Neurodiversity-Affirming Practices are a Moral Imperative for Occupational Therapy - Aaron R. Dallman; Kathryn L. Williams; Lauren Villa (Scholarworks @ WMU, 2022)
The term neurodiversity encompasses neurological differences such as clinical labels of autism, learning disabilities, synesthesia, hyperactivity disorders, and more. Proponents of the neurodiversity movement argue that current therapeutic and medical practices often attempt to "normalize" behaviors and ways of participation that originate from these differences in neurology and contribute to an individual's sense of identity. This paper argues that an ethical and morally just occupational therapy practice should affirm neurodivergent ways of being, and that occupational therapists must be active agents of change by listening to and collaborating with their neurodiverse clientele. We focus the discussion on our work with autistic individuals and consider past and current practice trends, including applied behavioral analysis, in light of various ethical mandates for occupational therapy. We conclude with suggestions for core tenets of neurodiversity-affirming occupational therapy practice with the hope that clinicians can apply these concepts to their clinical work and recognize how meaningful participation can be achieved by creating goals and interventions through a neurodiversity framework.